Patterns of Consumption Across a Caribbean Seascape: Roles of Habitat and Consumer Species Composition Through Time - Ritter, Carmen J.; Harper, Leah M.; Lefcheck, Jonathan S.; Paul, Valerie J.; Whippo, Ross; Jones, Scott; Ogburn, Matthew B.; Duffy, J. Emmett (Frontiers in Marine Science, 2021)
Herbivores, omnivores, and predators transfer energy and structure the communities of many coastal marine ecosystems, and the intensity with which they consume prey and contribute to ecosystem functioning varies substantially among habitats over short time periods. Whether generalities across habitats might emerge for longer time series and using standard methods remains largely untested. Here, we deployed standardized assays of consumption using dried squid (“squidpops”) and five common macrophytes (“weedpops”) to quantify consumption across coral fore reef and patch reefs, mangroves, seagrass meadows, and bare sand from 2015 to 2019 around Carrie Bow Cay, Belize. We also used video in 2017 to identify the species responsible for consumption. We found that both squid- and weedpop consumption were consistently highest on patch and fore reef habitats, moderate in mangroves, and lowest in seagrass and sand across all years of the survey. Videos showed that the majority of consumption on the reefs in 2017 could be attributed to < 5 fish species, and the identity of the dominant consumers differed among habitats. This study validates a key but implicit assumption in marine ecology that relative patterns in consumption across habitats are consistent through space and time in tropical nearshore environments, and reveals that high consumption rates may be the consequence of one or few species in each location.